The Impact of the Attractive Authority of High School Teachers in Developing the Leadership Skills of Students in Jordan - Alshawabkeh, Nabeela Abdallah Ghaithian (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying the effect of the attractive anthorety among secondary school teachers in developing the leadership skills of students in Jordan. The study sample consisted of (327) male and female teachers and (1130) male and female students at (6) male and female secondary schools distributed over the Kingdom’s three regions (the North Region, the Central Region and the South Region), the sample was selected based on the cluster random method, The researcher used the analytical descriptive approach since it suits the nature of the study, To achieve the objectives of the study, the researcher has developed a questionnaire to collect the needed data. And the study reached a number of results: the effect of the availability of the power of attractive among secondary stage teachers came at a medium level. The level of the availability of leadership skills among the secondary school students also came at a medium level. The results showed a positive effect of the attractive authorety on the development of leadership skills, moreover; there are statistically significant differences in the relationship between the attractive authority among the secondary stage students and the development of leadership skills of the students attributed to gender variable, where the result came in favor of males, and there were no statistically significant relationship attributed region variable.Based on the results, the researcher recommended a number of related recommendations, among which were the importance of training female teachers on the leadership skills in order to develop the skills of the female students, and the inclusion of a new subject in the secondary school curriculum that handles life skills such as leadership and problem solving.